1993
DOI: 10.1121/1.406719
|View full text |Cite
|
Sign up to set email alerts
|

Scattering by objects buried in underwater sediments: Theory and experiment

Abstract: The scattering of sound by objects buried in underwater sediments is studied in the context of an exactly soluble model. The model consists of two fluid half-spaces separated by a planar, fluid, transition layer of arbitrary thickness. Attenuation is included in any of these regions by using complex wave numbers. A directional source field, generated in the upper half-space by a continuous line array, insonifies an object placed in the lower half-space. The scattered field detected by another line array placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 6 publications
2
37
0
Order By: Relevance
“…For simple near-spherical target shapes proud or buried in a flat ocean bottom, scattering predictions are generated from high-fidelity solutions based on the T-matrix method [4]. Last year [5],…”
Section: Approachmentioning
confidence: 99%
“…For simple near-spherical target shapes proud or buried in a flat ocean bottom, scattering predictions are generated from high-fidelity solutions based on the T-matrix method [4]. Last year [5],…”
Section: Approachmentioning
confidence: 99%
“…For example, elimination of the first assumption is necessary to take into account scatterers located on the bottom surface or not buried completely but rather exposed in the water. In this case, analytical solutions are complicated, but can be analyzed numerically [Lim et al 1993and Lim 1998, Fawcett 1996, Fawcett and Lim 2003, Zampolli et al 2008. There is also a simpler semi-phenomenological approach, using ray considerations, that can be useful at high enough frequencies.…”
Section: °30mentioning
confidence: 99%
“…A sound wave that reaches the interface not only is reflected by the surface of sea bottom but also is affected by refraction and scattering. Lim et al [3] concluded that if the beam is scanned over the object at shallow grazing angles, the scattering of evanescent waves may be an important part of the received echo.…”
Section: Introductionmentioning
confidence: 99%
“…Swift and Stephen [2] computed the two-dimensional scattered field by the finite-difference method for an incident Gaussian pulse beam at 15 grazing angle. Lim et al [3] studied the scattering of sound by objects buried in underwater sediments in the context of an exactly soluble model. The main problem in studying the detection of a buried object is existence of the interface between the water and the sediment.…”
Section: Introductionmentioning
confidence: 99%